Chronic thrombocytopenia and outcomes following surgery for metastatic spinal tumors: An analysis of the United States Nationwide Inpatient Sample 2005–2018 - Yu-Tse Liu; Ting-Wei Chang; Cheng-Chi Lee; Ching-Chang Chen; Chun-Ting Chen; Mun-Chun Yeap; Yu-Chi Wang (Journal of Orthopaedic Surgery)
Background Thrombocytopenia leads to increased postoperative complications and mortality in elective surgeries. Questions/purposes Specific roles of thrombocytopenia on outcomes in orthopedic surgery remain relatively unexplored. This study aimed to assess the impact of chronic thrombocytopenia on outcomes of metastatic spinal tumor surgery. Patients and Methods Data from the United States Nationwide Inpatient Sample database 2005 to 2018 were examined. Patients ≥20 years old with metastatic spinal tumors undergoing surgery were identified. Propensity score matching (PSM) was used to balance the baseline characteristics between patients with and without chronic thrombocytopenia. Associations between chronic thrombocytopenia and hospitalization outcomes were determined by logistic regression analyses, adjusted for demographic and clinical factors. Results After PSM, a total of 8915 patients were included in the analysis. Chronic thrombocytopenia was associated with increased risk of in-hospital mortality (adjusted odds ratio [aOR] = 2.28; 95% confidence interval [CI]: 1.82-2.86), prolonged length of stay (aOR = 1.89; 95% CI: 1.67-2.14), non-home discharge (aOR = 1.52; 95% CI: 1.35-1.71), and perioperative complications (aOR = 3.14; 95% CI: 2.79-3.54) compared to no chronic thrombocytopenia (all, p < .001). Chronic thrombocytopenia was also significantly associated with increased risk of acute respiratory distress (ARDS) syndrome/respiratory failure (aOR = 2.49), tracheostomy/mechanical ventilation (aOR = 2.49), acute kidney injury (AKI) (aOR = 1.71), venous thromboembolism (aOR = 1.87), transfusion (aOR = 2.41), acute postoperative hemorrhagic anemia (aOR = 2.44), hematoma/seroma (aOR = 2.13), shock (aOR = 2.74), and sepsis (aOR = 1.56). Conclusion Chronic thrombocytopenia is a strong independent predictor of worse outcomes following surgery for metastatic spinal tumors. Clinical Relevance When managing these patients’ careful consideration of thrombocytopenia is imperative for informed decision-making.